Práticas e conhecimento dos educadores infantis sobre alimentação complementar nos Centros Municipais de Educação Infantil de Foz do Iguaçu/PR - Trevisan, Carina Loureiro (2017)
Complementary feeding usually begins outside the recommended period and often with inadequate nutritional balance and risks of contamination of microorganisms. The period of progressive introduction of food should occur between six and twelve months of life, and this stage is considered critical because it often leads to health problems when the child does not receive an adequate diet. The school is an inducer of healthy food practices, especially when it comes to public day care, because it is an environment in which the child spends a good part of his day. In this context, the teacher has an indispensable role in the promotion of children's health and requires qualified training in order to contribute to the adequate supply of complementary food, as advocated by the Ministry of Health. Given the complexity of the factors involved in feeding a child, this research had as objective to identify the knowledge and practices of children educators in relation to complementary feeding of nurseries of the Municipal Centers of Early Childhood Education (CMEI) of Foz do Iguaçu / PR. It was a qualitative study, using the Collective Subject Discourse (DSC) technique proposed by Lèfreve and Lèfreve, carried out in the first half of 2016, through semi-structured interviews with twenty-one children educators from thirteen CMEI's who nursery classes with children from six months to two years of age. As a result, Collective Subject Discourses regarding the consumption of industrialized foods by the children, presence of the discussion about the topic of healthy eating only on specific dates and the inability of the educators to deal with situations of need of specific feeding appeared. There was also a lack of knowledge on the part of the educators regarding complementary food, as well as the lack of technical support for the provision of meals at the Municipal Center for Early Childhood Education (CMEI's). Faced with this reality, the need for a restructuring in school feeding policy, as well as the elaboration and execution of training programs on nutrition education for educators, with continuous supervision of the effects of training as a strategy for improvement in the field of adequate nutrition.